Vedere lontano: cinema ed educazione alla geografia nell’Italia degli anni Dieci - Alovisio, Silvio; Mazzei, Luca (Cinergie – Il Cinema e le altre Arti, 2016)
This paper intends to address certain issues related to the role of scholastic geography within the intense debate on educational cinema in Italy in the 1910s and 1920s. If Italian educational geography is strategic in the construction of a national identity, what is the possible contribution of cinema to this project? Is such a project hegemonic in the reflection on educational projections or do other conceptions of environment, territory, travel and discovery of otherness exist? What features of innovative education are put forward for animated images, compared not only to cartographic images but also to the recent tradition represented by fixed projections, in which the function of the teacher turns out to be central?